Pengaruh Pendidikan dan Pelatihan, Tunjangan, Beban Kerja Terhadap Kinerja ASN - Angka, Andi FItri Sugi; Sutina, M. Muhajir (Jurnal Ilmiah Multidisiplin Amsir, 2023)
This study aims to determine and discover the relationships between education and training, allowances, workload, and the performance of civil servants (ASN) at KPKNL Parepare, both individually (partial) and collectively (simultaneous). The analysis method used is Multiple Linear Regression Analysis, Validity Test, Reliability Test, Partial Test (t-test), Simultaneous Test (F-test), and Coefficient of Determination Test (R2) with a population of 32 individuals and a sample size equal to the population using a saturated sampling technique. The research results based on data analysis show that, individually, education and training (X1) do not have a significant effect on performance (Y). This is evidenced by the Sig. value of 0.150 > 0.05 and the t-value of -1.482 < t-table 2.048.. Furthermore, collectively, all X variables (education and training, allowance, and workload) have an influence on the Y variable (performance) based on the F-test results with an F-value of 23.505 > F-table 2.93.